Service-learning and SDG 17: A qualitative analysis of community partnerships at DLSU Laguna - Palmones, Henry B., Jr. (Animo Repository, 2025)
Service-learning is a teaching method that requires linking community service to academic application to create a procedural way through which students relate the theoretical aspects of learning in the classroom with actual applications and to meet the identified specific needs of the local communities while Sustainable Development Goals 17 (SDG 17) emphasizes partnerships for the cooperation of people and organizations to mobilize resources, knowledge, skills, and resources to advance sustainable development goals. Both programs have a common goal: to develop sustainable development for the community. This qualitative research utilized thematic and content analysis together with qualitative document analysis (QDA) to assess the role of the Senior High School Service Learning Program (SHSSLP) of De La Salle University Laguna (DLSU Laguna) in promoting sustainable communities. Documents that were examined include syllabi of courses and guidelines of the program, descriptions of the projects, partnership agreements, journals of the students, and evaluation forms of the community partners. These documents provided an overall picture of the SHSSLP on how it approached engaging with the communities, the collaborative experiences of stakeholders, and the program's alignment with SDG 17 principles, which entails strengthening partnerships for implementation, innovative technological support, and resource mobilization. The progress reports and post-implementation evaluations provided additional information on achieving the program's outcomes and assessing its effectiveness after the implementation. The results and findings show that the DLSU Laguna’s SHSSLP helps in enabling effective community engagement, sharing knowledge and mutual learning, promoting effective resolution of organizational and community challenges, promoting capacity building and resilience in communities, and supporting the achievement of SDG 17, with its implications that the community partners describe the organization as an indispensable foundation for fostering service-learning with the DLSU Laguna SHSSLP. Through service-learning as a component of the academic program, the community partners could access institutional resources while the students and faculty learned from local perspectives. This qualitative document analysis of the SHSSLP at DLSU Laguna provides valuable insights into the university's efforts to foster sustainable community partnerships aligned with SDG 17 - Partnerships for the Goals.